Omental lymphangioma: a rare case report - Dahal, Geha Raj (Journal of Chitwan Medical College, 2020)
Lymphangioma is a common pediatric problem. Most of the lymphangiomas occur in head and neck region. Lymphangioma arising from omentum is extremely rare. It is a benign condition but is locally invasive. Symptoms usually arise from its mass effect or complications. Complete excision including removal of all loculi is necessary for cure. We report such a case of omental lymphangioma in a six-year boy.